Economic Assessment of Significance of Education in the Development of a Knowledge-Based Economy - Ignjatijevic, Svetlana; Cogojević, Maja; Milenković, Nikola (Industrija, 2018)
Research subject is an analysis of the role of education in development of a country, with a goal to look at all differences in views of examinees employed in the economy, educational institutions and students on the role of the government, economy and educational institutions in economic development. Research was conducted in Serbia, Croatia and Macedonia in 2014, by using a survey method. Research results have shown that there is a difference in opinions about the role of the public and private sector in education, depending on where examinee lives, while on the other hand difference in employment is not affecting the difference in their views. When the role of educational institutions and education itself is in question, research showed that there are no differences between Serbian, Croatian and Macedonian examinees. Although there is a difference between examinees according to their employment and it’s the biggest between students, while there is no big difference between employed examinees.
Keywords: Evaluation; Educational institution; Education; Economy; Economics